2021
DOI: 10.1088/1361-6463/ac2fda
|View full text |Cite
|
Sign up to set email alerts
|

Sound insulation properties of membrane-type acoustic metamaterials with petal-like split rings

Abstract: Membrane-type acoustic metamaterials (MAMs) are lightweight and flimsy materials with excellent low-frequency insulation performance, which breaks the limitations of the traditional mass law and provides a new idea for noise reduction in the low-frequency range. To further broaden the sound insulation bandwidth on the premise of lightweight design, a novel MAM with petal-like rings is proposed, and the parametric studies on the structural parameters of split rings are carried out in this paper. By combining th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…It is easy to see from Figure 11a that, when the mass block was placed eccentrically, its STL curve was shifted, but the magnitude of the main peaks and valleys (the peaks and valleys produced when the mass is coincident with the film center of mass) and the frequency bands generated did not change much; when the mass block was placed too close to the film boundary, its STL was significantly shifted. Whereas this differs from the behavior of the cylindrical mass block, which produces more peaks and valleys when eccentric [7][8][9][12][13][14][15][16][17][18][19][20], these additional sound insulation summits affected the frequency band and size of the main peaks. It was shown that the hexagonal cone mass block had a more stable sound insulation effect in the lower frequency band.…”
Section: Different Defect States Of Hexagonal Conementioning
confidence: 97%
See 1 more Smart Citation
“…It is easy to see from Figure 11a that, when the mass block was placed eccentrically, its STL curve was shifted, but the magnitude of the main peaks and valleys (the peaks and valleys produced when the mass is coincident with the film center of mass) and the frequency bands generated did not change much; when the mass block was placed too close to the film boundary, its STL was significantly shifted. Whereas this differs from the behavior of the cylindrical mass block, which produces more peaks and valleys when eccentric [7][8][9][12][13][14][15][16][17][18][19][20], these additional sound insulation summits affected the frequency band and size of the main peaks. It was shown that the hexagonal cone mass block had a more stable sound insulation effect in the lower frequency band.…”
Section: Different Defect States Of Hexagonal Conementioning
confidence: 97%
“…Guancong Ma et al [6] established a membrane-type metamaterial structure with cavities to increase the noise reduction effect of the structure by using hybrid resonance. Huang et al [7] proposed a petal-shaped circular membrane-type metamaterial that is lighter than the cylindrical structure while ensuring certain STL effect. Lu et al [8] Materials 2022, 15, 1556 2 of 16 investigated the STL in the eccentric state of the mass block and introduced a preparation technique to accurately apply tension to the film.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [ 23 ] designed a symmetrical cross-shaped mass block structure that is easy to achieve dynamic balance according to the low-order vibration characteristics and realized multi-state continuous sound insulation peaks. On the basis of Zhou’s model, Huang et al [ 24 ] proposed a new MAM with petal-like rings, which achieved a similar sound insulation effect under lighter mass conditions. Lu et al [ 25 ] designed a mass block in the form of split rings, which can obtain better acoustic performance through optimization of the distribution of eccentric masses.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane-type structures are an important type of local resonant acoustic metamaterials with the advantages of lightweight, small size, and high pertinence, [14][15][16] which are widely used in the field of low-frequency sound insulation. Membrane resonators achieve acoustic effects similar to those of Helmholtz resonators through a different mechanism.…”
Section: Introductionmentioning
confidence: 99%